Technology-enhanced learning in Asia: New educational possibilities for the tomorrows doctors and tomorrows cures - Majumder, Md Anwarul Azim; Rahman, Sayeeda; Azim, Md Sayed Shehran (South East Asia Journal of Public Health, 2015)
South East Asia Journal of Public Health Vol.4(2) 2014: 55-58